Secondary use of routine data in hospitals: description of a scalable analytical platform based on a business intelligence system. Issue 2 (20th September 2018) - Roth, Jan A; Goebel, Nicole; Sakoparnig, Thomas; Neubauer, Simon; Kuenzel-Pawlik, Eleonore; Gerber, Martin; Widmer, Andreas F; Abshagen, Christian; Padiyath, Rakesh; Hug, Balthasar L; ,
Abstract: We describe a scalable platform for research-oriented analyses of routine data in hospitals, which evolved from a state-of-the-art business intelligence architecture for enterprise resource planning. This platform involves an in-memory database management system for data modeling and analytics and a high-performance cluster for more computing-intensive analytical tasks. Setting up platforms for research-oriented analyses is a highly dynamic, time-consuming, and costly process. In some health care institutions, effective research platforms may be derived from existing business intelligence systems.